Introduction: towards a conception of 'literary theory of uncertainty' - Høeg, ML (Bloomsbury Publishing, 2021)
Uncertainty of meaning is a fundamental dimension and quality of literature and constitutive of what renders some literary works accessible, appealing and engaging across time and in different contexts. Uncertainty is a precondition for literature, indeed for any stabilization of meaning. A greater or lesser degree of authorial and readerly awareness of this precondition and fundamental trait is possible, and, thus, uncertainty can also form part of a narrative strategy and function as a literary device, used either to disrupt the seeming naturalness of a narrative or as a mimetic method to authentically render the uncertainty of reality and human perception. And uncertainty can be integrated into a critical reading strategy or interpretational attitude by which the fundamental uncertainty of narrative is acknowledged and the uncertainties and inherent tensions of a literary narrative are kept open and unresolved. The notion of uncertainty of meaning has always existed and been relevant, if not in the form of explicitly recognized and theorized concepts, then implicitly present as the defining opposition of certain and decided meaning. In this sense, all theory of literature, interpretation and meaning is also theory of uncertainty. However, in the nineteenth century through the twentieth, the ideas of, and thinking about, uncertainty begin to consolidate into a more distinct branch in literary theory. This growing preoccupation in literature and literary theory with uncertainty of meaning and interpretation is linked to a general shift in how the world and human existence is perceived and to developments in the fields of physics, philosophy and psychology. As a new scientific view of the physical world emerges in the beginning of the twentieth century, notions of uncertainty become increasingly prevalent in all spheres of society, and scientific truth about the world and the human perception of it as well as the artistic representations and explorations of these undergo a noticeable change. ...